2005
DOI: 10.1124/jpet.105.098566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subchronic Treatment of Memantine, Galantamine, and Nicotine in the Brain of Tg2576 (APPswe) Transgenic Mice

Abstract: An increasing number of studies suggest that the present clinical therapy used in Alzheimer's disease (AD), in addition to having a symptomatic effect, also may interact with the ongoing neuropathological processes in the brain. The aim of this study was to investigate the effect of the cholinesterase inhibitor galantamine and the N-methyl-D-aspartate (NMDA) antagonist memantine in comparison to nicotine on the neuropathology of Tg2576 transgenic mice (APPswe). Nontransgenic and APPswe mice at 10 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 37 publications
6
39
1
1
Order By: Relevance
“…Our results are consistent with previous studies which found decreases in cortical APP levels in Tg2576 mice after 10 days of memantine treatment (Unger et al, 2006). However, the mechanism by which memantine regulates amyloid metabolism is not clear.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are consistent with previous studies which found decreases in cortical APP levels in Tg2576 mice after 10 days of memantine treatment (Unger et al, 2006). However, the mechanism by which memantine regulates amyloid metabolism is not clear.…”
Section: Discussionsupporting
confidence: 83%
“…Saxena et al (2011) have shown that a 14-day chronic Nic treatment in icv-STZ-treated animals avoids mitochondrial dysfunctions and caspase-3 activity, evidencing the Nic protective influence against apoptosisrelated processes. Our findings, together with those from Srivareerat et al (2011), are in agreement with multiple reports on Nic neuroprotective roles (Fujii and Sumikawa, 2001;Picciotto and Zoli, 2002;Liu and Zhao, 2004;Unger et al, 2006;Poorthuis et al, 2009). In addition, it has been shown that neuroprotection is blocked by nAChR antagonists (Akaike et al, 2010), and that nicotinic receptors can modulate mnemonic processes involving ACh release and Ca 2+ homeostasis (Se´gue´la et al, 1993;McGehee et al, 1995).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to earlier studies [22,35] , we did not observe any significant changes in synaptophysin levels in the APPswe mice compared with nontransgenic controls. A possible explanation might be the use of another mouse genetic background strain (C6/SJL) compared with C57B6 in the previous studies.…”
Section: Discussioncontrasting
confidence: 56%